Italian policy towards cooperation in R&D - Maria Rosa Battaggion; Patrizia Bussoli (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper explores the various policies implemented in Italy to foster innovative activities and to regulate the technological effects on market competition and Intellectual Property Rights (IPR). Research promotion has primarily taken the form of facilitated credits and grants to stimulate R&D and to speed up the diffusion of technological knowledge. The analysis of governmental instruments used for the promotion of R&D cooperation shows that a specific and coherent strategy to sustain Research Joint Ventures (RJVs) does not exist yet in Italy. However, in the last decade Italian firms and research centers/universities have been actively involved in the programs financed by the European Commission. Italian Antitrust Policies and Intellectual Property Rights mainly derive from European legislation. The analysis proposed shows that there are no specific features discouraging or encouraging the creation and the performance of RJVs.
Keywords: L4; L5; O34; 330; R&D policy; R&D cooperation; intellectual property rights; patent system; antitrust policy; Italy; Forschungskooperation; Forschungs- und Technologiepolitik; Konzentrationspolitik; Immaterialgüterrechte; Italien